A Problem Encountered in the Comparison of Technical Coefficients - Wurtele, Zivia S. (Review of Economic Studies, 1959)
Journal Article A Problem Encountered in the Comparison of Technical Coefficients Get access Zivia S. Wurtele Zivia S. Wurtele Cambridge, Mass. Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 26, Issue 2, February 1959, Pages 148–152, https://doi.org/10.2307/2296172 Published: 01 February 1959